Purchase Decision: Role of Price and Service Quality - Yayu Kusdiana; Arie Yusnelly; Nanda Suryadi (Yayasan Pendidikan Islam Al-Matani, 2023)
The primary objective of this research was to examine the impact of pricing and service quality on consumer purchasing decisions specifically at the Noer Abadi store. This study was conducted with a carefully selected sample of 82 respondents, utilizing a purposive sampling technique to ensure the sample's relevance and suitability to the research question. Data collection was carried out using a mixed-method approach, incorporating both primary and secondary data to provide a comprehensive view. The data analysis was performed using a multiple linear regression technique, a robust statistical tool that can provide insight into the relationship between multiple variables. The findings of the study indicate that both price and service quality exert a significant and positive influence on purchase decisions. This effect was observed on both an individual level (partially) and when considered together (simultaneously), suggesting that both factors are crucial considerations for consumers at the Noer Abadi store.